Macrophage-derived netrin-1 promotes abdominal aortic aneurysm formation by activating MMP3 in vascular smooth muscle cells. Issue 1 (December 2018) - Hadi, Tarik; Boytard, Ludovic; Silvestro, Michele; Alebrahim, Dornazsadat; Jacob, Samson; Feinstein, Jordyn; Barone, Krista; Spiro, Wes; Hutchison, Susan; Simon, Russell; Rateri, Debra; Pinet, Florence; et al.
Abstract Abdominal aortic aneurysms (AAA) are characterized by extensive extracellular matrix (ECM) fragmentation and inflammation. However, the mechanisms by which these events are coupled thereby fueling focal vascular damage are undefined. Here we report through single-cell RNA-sequencing of diseased aorta that the neuronal guidance cue netrin-1 can act at the interface of macrophage-driven injury and ECM degradation. Netrin-1 expression peaks in human and murine aneurysmal macrophages. Targeted deletion of netrin-1 in macrophages protects mice from developing AAA. Through its receptor neogenin-1, netrin-1 induces a robust intracellular calcium flux necessary for the transcriptional regulation and persistent catalytic activation of matrix metalloproteinase-3 (MMP3) by vascular smooth muscle cells. Deficiency in MMP3 reduces ECM damage and the susceptibility of mice to develop AAA. Here, we establish netrin-1 as a major signal that mediates the dynamic crosstalk between inflammation and chronic erosion of the ECM in AAA. Abdominal aortic aneurysms (AAA) are characterized by extensive extracellular matrix degradation. Here Hadi et al. identify a netrin-1/neogenin-based crosstalk between macrophages and vascular smooth muscle cells (VSMCs), leading to the secretion of the matrix metalloproteinase MMP-3 by VSMCs and subsequent matrix degradation in AAA lesions.